Assessing the association of severe malaria infection and ABO blood groups in northwestern Ethiopia - Hailu Tadesse (Journal of Vector Borne Diseases, 2013)
Background & objectives: There is lack of adequate information on the association between severe malaria and some human genetic markers like ABO blood types. The study was undertaken to evaluate the association between severe malaria infection and ABO blood types among febrile patients attending Felegeselam Health Center, northwestern Ethiopia. Methods: A total of 398 febrile patients were examined for malaria and tested for ABO blood groups in December 2011. The blood samples were collected by finger pricking, stained with Giemsa and slides were examined microscopically. ABO blood group was determined by agglutination test using agglutinating A and B monoclonal anti-sera together with parasite load count. Chi-square and ANOVA tests were used to assess the difference between frequencies and means, respectively. Results: Out of 398 acute febrile patients, 201 (50.5%) were found to be infected with Plasmodium parasites. Of which 194 (48.74%) and 7 (1.76%) belong to Plasmodium falciparum and P. vivax, respectively. The distribution of ABO blood groups was O (46%), A (27.1%), B (23.1%) and AB (3.8%). The percentage of severe malaria with respect to blood group A, B, AB and O was found to be 40, 34.1, 14.3 and 5.1%, respectively. The association of severe malaria with non 'O' blood types was statistically significant (χ2 = 31.246, p <0.01). Interpretation & conclusion: The present findings indicate that individuals with blood groups A, B and AB are more susceptible for severe malaria infection than blood group O.